2019
DOI: 10.1111/jcmm.14683
|View full text |Cite
|
Sign up to set email alerts
|

Caspase recruitment domain family member 10 regulates carbamoyl phosphate synthase 1 and promotes cancer growth in bladder cancer cells

Abstract: Bladder cancer, which can be divided into non‐muscle‐invasive and muscle‐invasive bladder cancer, is the most common urinary cancer in the United States. Caspase recruitment domain family member 10 (CARD10), also named CARD‐containing MAGUK protein 3 (CARMA3), is a member of the CARMA family and may activate the nuclear factor kappa B (NF‐κB) pathway. We utilized RNA sequencing and metabolic mass spectrometry to identify the molecular and metabolic feature of CARD10. The signalling pathway of CARD10 was verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…CPS1 upregulation may be multi-faceted depending on the tissue of origin: in non-small-cell lung carcinomas, liver kinase B1/AMPK-mediated CPS1 transcriptional repression is lost, allowing the gene to be transcribed 48 . In bladder cancer, caspase recruitment domain family member 10 (CARD10), via nuclear factor kappa B (NF-κB), activates CPS1 expression 88 .…”
Section: Cps1 In Diseasementioning
confidence: 99%
“…CPS1 upregulation may be multi-faceted depending on the tissue of origin: in non-small-cell lung carcinomas, liver kinase B1/AMPK-mediated CPS1 transcriptional repression is lost, allowing the gene to be transcribed 48 . In bladder cancer, caspase recruitment domain family member 10 (CARD10), via nuclear factor kappa B (NF-κB), activates CPS1 expression 88 .…”
Section: Cps1 In Diseasementioning
confidence: 99%
“…2 F) [ 28 ]. Besides, EMS altered the expression of apoptosis-related genes, such as the decrease expression of anti-apoptosis genes including TRAF2 [ 29 ], CARD10 [ 30 ], and the increase of pro-apoptosis gene expression including CASP3, RHOB [ 31 ], and FOXO3 [ 32 ] (Fig. 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, we do not have data to show whether FMO3 regulates transcription of Cps1 or protein stability of it. Furthermore, it has been reported that NFKB, a transcription factor that can be activated by TMAO [15], induced expression of CPS1 in bladder tumor cell lines [88]. As the result, whether TMAO is involved in FMO3-regulated expression of Cps1 remains unclear.…”
Section: Discussionmentioning
confidence: 99%